2018
DOI: 10.3390/pr6090152
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Flow Coupled Behavior of Artificial Joints with Sawtooth Asperities

Abstract: The coupling between hydraulic and mechanical processes in rock joints has significantly influenced the properties and applications of rock mass in many engineering fields. In this study, a series of regular shear tests and shear-flow coupled tests were conducted on artificial joints with sawtooth asperities. Shear deformation, strength, and seepage properties were comprehensively analyzed to reveal the influence of joint roughness, normal stress, and seepage pressure on shear-flow coupled behavior. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For rock brittle materials, not only tensile failure but also shear failure affects the growth of cracks. The crack tip will also have N stress perpendicular to the crack surface (Zhao et al, 2012;Cheng and Zhou, 2015;Wei et al, 2017;Zhao et al, 2018;Guo et al, 2019;Liu et al, 2019;Li H. F et al, 2021;Wang and Zhao, 2021). Therefore, it is necessary to focus on studying the law of crack propagation after crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…For rock brittle materials, not only tensile failure but also shear failure affects the growth of cracks. The crack tip will also have N stress perpendicular to the crack surface (Zhao et al, 2012;Cheng and Zhou, 2015;Wei et al, 2017;Zhao et al, 2018;Guo et al, 2019;Liu et al, 2019;Li H. F et al, 2021;Wang and Zhao, 2021). Therefore, it is necessary to focus on studying the law of crack propagation after crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the permeability increases fast at the beginning of shear deformation, and then the growth continues at a lower rate until to the limit value. Olsson and Barton [20], Shi et al [21], and Zhao et al [22] adopted osmotic pressure to conduct shear-flow coupling test on rock fracture, and empirical formulas regarding the effect of contact area and surface roughness on fluid flow behavior were established. Zhang et al [23] investigated the shear-induced permeability evolution in saw-cut sandstone fractures under triaxial stress condition.…”
Section: Introductionmentioning
confidence: 99%